Metabolic features of patients with repeated Omicron infections highlight new targets for therapeutic intervention - Jiaying Zhang; Sin Man Lam; Shan Ji; Longyu Zhang; Jiming Yin; Haiqing Sun; Danlei Mou; Lianchun Liang; Qinghua Meng; Guanghou Shui; Yingmei Feng (Scientific Reports)
Abstract Emerging evidence underscores the role of metabolites in immunomodulation. We surmise that specific metabolic signatures might be conserved during repeated Omicron infections. To verify our hypothesis, patients with first (n = 28) and repeated Omicron infections (n = 38) between November 2023 to April 2024 were recruited into this study. Healthy controls (n = 20) were enrolled in the same period. Comprehensive serum metabolome and lipidome were quantitated using mass spectrometric approaches. The neutralizing activity of sera against the pseudotyped Omicron variant JN.1 was determined. Circulating cytokines/chemokines were quantified using a Bioplex Kit Assay. The proportion of severe/moderate infections was 2.9-fold higher in first infection patients compared to reinfection patients (67.9% vs. 23.7%, p = 0.004). Geometric mean titers (GMT) for the Omicron variant JN.1 were higher in moderate/severe infections than mild infections, but non-significant between first and repeated infections. We observed perturbed coregulation between plasma indoles and circulating plasmalogen phospholipids in Omicron-infected patients, while disrupted histidine-triacylglycerol coregulation was specific to first-infections. A panel of three lasso-selected metabolites (SL d18:1/22:0 h, tetra-peptide Pro Tyr Tyr Val, and 1,2,3,4-Tetrahydroisoquinoline) effectively differentiated moderate/severe Omicron infections from mild ones (AUROC at 0.917, 95% CI 0.793-1.000). Our findings highlight modifiable metabolic signatures as possibly new therapeutic interventions against rapidly evolving variants of SARS-CoV-2.